Pembekalan Soft Skill dalam Perencanaan SDM, Rekrutmen dan Manajemen Karir Bagi Siswa SMK Negeri 8 Pandeglang - Abdullah Ridho; Mohammad Mahrus Mahjumi; Muhammad Arifin; Kasifah Kasifah; Khairunnisa Tri Azizah Wati (Yayasan Literasi Sains Indonesia, 2026)
(Soft skill development in human resource (HR) planning, recruitment, and career management is a strategic step in preparing a competent and competitive young generation. Vocational High Schools (SMK) as vocational education institutions play a crucial role in producing work-ready graduates. However, many SMK students still lack adequate understanding of the importance of soft skills, employment recruitment procedures, and structured career planning. This Community Service Activity (PKM) was conducted at SMK Negeri 8 Pandeglang with the aim of improving students' understanding, readiness, and confidence in facing the world of work through an interactive training approach. The methods used include socialization, material presentations, interactive discussions, and job interview simulations. Approximately 50 students from the Finance department participated. Results showed significant improvements in students' understanding of soft skills and work readiness, as well as increased motivation in career planning. A partner satisfaction survey showed an average score of 4.38 out of 5, reflecting a satisfaction level between Satisfied and Very Satisfied. This activity is expected to serve as a model for sustainable mentorship between higher education institutions and vocational high schools.